Anodic Stability of New Sulfone‐Based Electrolytes for Lithium‐Ion Batteries. Issue 16 (30th May 2018) - Flamme, Benjamin; Haddad, Mansour; Phansavath, Phannarath; Ratovelomanana‐Vidal, Virginie; Chagnes, Alexandre
Abstract: Twenty‐two new bifunctional sulfones containing ester, ether and carbonate moieties have been synthesized in the present work. Their physicochemical properties [dynamic viscosity, ionic conductivity in the presence of lithium bis‐trifluoromethanesulfonimidate (LiTFSI), boiling and melting points] and their anodic stability have been investigated. Major drawbacks for the use of these sulfones in lithium‐ion batteries (LiBs) are their high viscosities and high melting points. Nevertheless, these solvents exhibit high anodic stability at platinum, glassy carbon, and NMC (LiNi1/3 Mn1/3 Co1/3 ) electrodes and their ionic conductivities in the presence of LiTFSI remain high enough to envisage their use in LiBs despite their high viscosities. In particular, 3‐methoxytetrahydrothiophene 1, 1‐dioxide (MESL) is the most interesting among the 22 synthesized sulfones, because MESL exhibits an oxidation potential at a NMC cathode in the presence of LiTFSI of 4.9 V vs. Li/Li +, an ionic conductivity equal to 1 mS cm −1, and a low melting point as well as a high boiling point. Abstract : Ad LiB : Physicochemical and electrochemical properties of new sulfones synthesized at the laboratory scale are investigated and presented.